Modification of Y-zeolite mesoporosity by ultrasonic-assisted technique as active catalysts for catalytic cracking of VGO - Rashied, Mohammed I.; Abd Alrubaye, Rana Th.; Abdulridha, Samer G. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
In this study, Pristine Y zeolite (CBV 400) of Si/Al )2.5( was treated to produce modified mesoporous zeolites. The process involved the aid of post-synthesis sequential dealumination in its conventional mode and ultrasonic-assisted desilication techniques. Both ethylene-diaminetetraacetic acid (EDTA) and oxalic acid (OX) were tested as chelating reagents in the dealumination step for 1, 3, and 6 h. The dealuminated samples of zeolite were treated sophisticatedly with sodium hydroxide NaOH in a water bath sonication at a frequency of 20 Hz and 65 ºC for different times of 5 and 15 min. Dealumination of the original zeolite by OX acid for 3h and desilication of the acid-treated sample with NaOH solution for 15 min has improved the mesoporosity by around 120% higher than the parent sample of Vmeso=0.08 m3/g. The modified sample has a mesopore volume (Vmeso) of 0.2 m3/g and an external surface area (Sexternal) of 89 m2/g. The resulting mesoporous zeolite was examined for stability measurements via thermal treatment at 550 ºC for 3h, which reveals high stability. Parent and modified zeolite were tested as heterogeneous catalysts for the catalytic cracking reaction with VGO and 1g catalyst load with different temperatures (from 400 to 420 °C) and a reaction time of 480 minutes. The reaction was carried out using a batch reaction system, and a higher yield of gasoline (about 44.44 vol%) was obtained using the modified zeolite (UDSY15-OX3) at 420 °C reaction temperature, as opposed to the direct use of the non-modified catalyst, which gives out only 18.4 vol% gasoline yield. Thus, commercializing the OX-NaOH pathway with the assistance of ultrasonic energy can decrease the treatment duration and energy consumption, producing a thermally stable mesoporous material to catalyze the cracking reactions of heavy oils.